Assessing the Impact of Homestay Tourism on Achieving SDG in Chitwan and Nawalparasi Districts, Nepal (OCEM Journal of Management, Technology & Social Sciences, 2026)
Community homestays in Chitwan and Nawalparasi district, Nepal, are important for boosting tourism and improving the economic conditions of local families. A homestay business enables tourists to stay with local families and learn about their culture, thereby helping hosts earn additional income. The homestay industry in Chitwan has significant potential to benefit both the local economy and tourism. However, differences in income across homestays and their effects on household income remain unexplored. This study examines the income generated by homestays and compares their economic conditions. The study is critical because it demonstrates how tourism can help individuals achieve greater financial stability and enhance their quality of life, particularly in rural Nepal.The goals are to compare the economic benefits of homestays and to examine their effects on SGDs (gender, proverty, economic growth, decent work). We used a quantitative survey to collect one hundred and fifty data from owners and employees of fifty homestays by administering survey instrument. Descriptive statistics were used to analyse the collected data. The results indicate that Community Homestay yields the most significant economic benefits, primarily due to improved marketing and visitor engagement. Households participating in homestays experienced annual income increases of 25%-40%, thereby improving their standard of living. The results also indicate a positive association between the homestay business and community economic development. The results are supportive to inform decisions on tourism policies and economic strategies. At the same time, tourism stakeholders (including NGOs and the Nepal Tourism Board) will receive guidance to plan the expansion of rural tourism programs nationwide.